Incidence of Needle Stick and Sharp Items Injuries Among Nurses At Al-Kindy Teaching Hospital - Batool Kadham Hussin, Zahraa Khalid Idaned (Pakistan Journal of Medical & Health Sciences, 2022)
Background: This paper aimed to assess the rate of NSIs among the Iraq nursing staff at Kindy teaching hospital Methods: A descriptive study was conducted to collect information about the rate of acupuncture accidents among nurses at Al-Kindi Teaching Hospital. Results: (77%) of the sample were in the stage group of 20-30 years. while the majority of the sample (74%) was female. Regarding the educational level, the high percentage of high school with 52%, followed by the institute of nursing with a 22% about experience years the majority of sample 70% were 1-5 years in hospital. Among the nurses involved in the study, 72% were injured in acupuncture sharps while 64% did not participate in training courses about NSIs Conclusion: Nursing workers suffer a high rate of sharp injuries, which can increase the chances of a disease and its consequences. Emphases of researcher’s mast increasing the nurses’ awareness and skills, holding workshops, finally, the importance of completing the hepatitis B vaccine course can be effective in reducing the incidence of infections and the risks of infectious diseases.